Analysis of Global Economic-Oriented Micro, Small and Medium Enterprises (SMEs) Mapping to Support the Success of Sustainable Development Goals (SDGs) Case study: Sukoharjo, Indonesia - Umrotun Umrotun; Priyono Priyono; Choirul Amin; Muhammad Sholahuddin (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2020)
Creative economy remains a critical issue for developing countries, including Indonesia. The Sustainable Development Goals (SDGs) show that the world agreed to boost the economy around the world. Micro, Small and Medium Enterprises (SMEs) creative industries are expected to compete in the global era, yet weak in the synergy between stakeholders. Previous researches have produced a map of the distribution of the creative economy in Sukoharjo Regency. Empirical and literature studies consist of three sections. First, it presents the potential creative economy of Sukoharjo Regency. Second, it discusses the various regulations, strengths, weaknesses, opportunities, and threats of the creative economy. Third, it presents various empirical studies about the creative economy. Literature study method was analyzed using content analysis to generate pre-analysis strengths, weaknesses, opportunities, and threats of the creative economy. The results of this study show that the creative economy in Sukoharjo Regency is potential for increasing the Gross Domestic Product of Regions. Besides, the study found local government regulations and identification of the strengths, weaknesses, opportunities, and challenges of creative economy in Sukoharjo Regency. In addition, the empirical study of strategies for improving the creative economy was also found. The results of this study need to be optimized to recommend a spotlight on the creative economy towards superior product.